The College Dropout and the Utilization of Talent - Pervin, Lawrence A.; Dalrymple, Willard; Reik, Louis E. (Princeton, NJ : Princeton University Press, 2015)
This book examines the complicated personal and institutional factors that influence a student's decision to terminate his studies; it investigates ways to enable him to resume his education and utilize his talents. The opening chapters approach the problem from an administrative point of view, reporting on statistical and psychological research and indicating future directions. Subsequent chapters deal with personal dimensions: relations between the student and his college environment; the effects of timing of readmission; family attitudes toward the dropout; the effectiveness of psychiatric treatment; personality traits that contribute to a student's difficulties. College administrators will find this study relevant to policy decisions on admissions, medical services, and course structuring. Clinicians and researchers will find guidelines for therapy and suggestions for further investigation. Finally, parents of college dropouts will gain new understanding of the problem and the best way to meet it.Originally published in 1966.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Foreword -- Contents -- Part I. Research and Administration -- Introduction: The Dropout in Conflict with Society -- 1. The Ontogeny of the Dropout Problem / Kubie, Lawrence S. -- 2. The Later Academic, Vocational, and Personal Success of College Dropouts / Pervin, Lawrence A. -- 3. A Critical Review of Research on the College Dropout / Knoell, Dorothy M. -- 4. College Dropouts: Successes or Failures? / Ford, Donald H. / Urban, Hugh B. -- Part II. The Personal Dimension -- Dear Parents -- 5. Personal Determinants and Their Interaction with the Environment -- 6. Readmission to College After Psychiatric Medical Leave / Peszke, Michael A. / Arnstein, Robert L. -- 7. Adaptation, Education, and Emotional Growth / Snyder, Benson R. -- 8. The College Dropout in Clinical Perspective / Reik, Louis E. -- 9. Some Socio-Cultural Issues in the Etiology and Treatment of College Dropouts / Levenson, Edgar A. -- 10. Talent as Danger: Psychoanalytic Observations on Academic Difficulty / Schafer, Roy -- 11. Identity and Depression in Students Who Fail / Harvey, William A. -- Conclusion -- Appendix. Programs and Selected Publications Relating to College Dropouts / Montgomery, James / Hills, John -- Contributors -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: College dropouts; EDUCATION / Higher